Jury Reform: Of Myths and Moral Panics - DUFF, Peter (Institutional Knowledge at Singapore Management University, 1997)
It is now commonplace to assert that the jury performs an important ideological or symbolic role in the criminal justice process. Indeed, it is often argued that this function is more significant than the impact the jury has in practice (see Mungham & Bankowski 1976; Duff & Findlay 1982; Findlay & Duff 1988: 1–7; Darbyshire 1991). Certainly it is true that, in virtually every jurisdiction where the jury exists, only a very small proportion of alleged offenders have their cases heard before a jury. There are two principal reasons for this. First, the vast majority of those charged with criminal offences simply plead guilty. Second, the great majority of those who assert their innocence are tried in the lower courts where the jury has no place or has long since been removed through the encroachment of summary jurisdiction or the expansion of ‘judge-alone’ trial. Consequently, the proportion of cases heard before a jury is astonishingly low given the significance with which the institution is usually vested and the community confidence which it generates. Why, then, is such importance attached to the institution of trial by jury?